Quantification of phenolic compounds and antioxidant capacity of an underutilized Indian fruit: Rayan [Manilkara hexandra (Roxb.) Dubard] - Bhumi Parikh; V.H. Patel (Food Science and Human Wellness)
The fruit of Manilkara hexandra (Roxb.) Dubard is one of the most underutilized fruits of India and in Gujarat state. It is popularly known as ‘Rayan’. The fruit and seed of Rayan were analysed for their total phenolic and flavonoid content, phenolic compounds and total antioxidant capacity with six different assay methods. The results indicated that the methanolic extract of Rayan fruit being a good source of phenolic (811.3 mg GAE/100 g fw) and flavonoid (485.56 mg RE/100 g fw) content. Also, eleven known phenolic compounds were tentatively identified for the first time from the fruit and seed of Rayan. The LC–MS/MS analysis of fruit revealed the presence of major phenolic compounds such as gallic acid, quercetin and kaempferol, while quercetin, gallic acid and vanillic acid in seed. The presence of quercetin suggests health benefits. The fruit of Rayan was also proved to be a better source of antioxidants as measured by FRAP, RPA, DPPHRSA, ABTSRSA and HRSA except NORSA in comparison with that of seed. The current study explains that M. hexandra is a relatively good source of antioxidants such as phenols and flavonoids for diet.